Filsafat dan Agama - Syatori, Ahmad; Ahmad Syatori, Syatori (Mahad Aly Al Fithrah, 2024)
Religion and philosophy are two components that direct humans in achieving life goals. It is this fundamental difference that gives rise to the tendency for symmetrical and non-reciprocal development between philosophy and religion in the field of modern